Fotolivro As Caras de Juventino Maravilha: corpo e máscara na composição dramática - Pereira, Jucinaldo Herculano (2023)
The aim of this research was to address the intersections between dramatic composition and the photobook. We are interested in the paths taken and involved in the language of dramaturgy by incorporating photobook techniques, either as a recording and memory generation mechanism or as a creative process, above all, based on the relationship between body and mask; and yet, to retrace the changes engineered in the field of photography when it gathers media resources, which establish convergences for a narrative in the dramaturgical composition. For that, the dramaturgy of Everaldo Vasconcelos was used, through the text “As Caras de Juventino Maravilha”, the free software GIMP for image processing and Scribus for electronic publishing, to produce the photobook and reflect on the relationships exercised between photography and staging. The practical and theoretical experiences of the researcher are highlighted, in relation to the body and the mask, from his encounter with theatrical art, to the meeting between the praxis of staging and the resources of photography for the elaboration of the artifact. This dissertation dialogues, reflects and is inspired by the theoretical conceptions of the authors: Bonfitto (2011), Stanislavisk (1997), Burnier (2009) in order to think about the function of the body in the actor's body. About the planning of the photobook and narrative articulations of photography, this study was inspired by the authors: Michael Freeman (2014), Gerry Badger (2015), Vilém Flusser (2009), Roland Barthes (1980) and Walter Benjamin (2012). The theoretical conceptions of the authors made it possible to analyze the contribution and potentialization of the photographic image, which is capable of intervening and creating a visible reality in dramaturgy.